ICETHK User's Manual, Version 1 - Tuthill, Andrew M.; Wuebben, James L.; Gagnon, John J. (1998)
This report describes the ICETHK computer model that is used in conjunction with the HEC-2 backwater model to simulate equilibrium ice jam profiles. The ICETHK model fulfills an important need in studies that require the calculation of ice jam affected stage. This report presents the theory and limitations of ICETHK and serves as a user's manual, and concludes with a discussion of river ice modeling using ICETHK.